PENGARUH PENERAPAN MODEL PROBLEM BASED LEARNING BERBANTUAN EDMODO PADA MATERI SISTEM PEREDARAN DARAH TERHADAP HASIL BELAJAR PESERTA DIDIK KELAS XI SMA NEGERI 8 PALEMBANG - Riefka Annisa Prilyta; Rahmi Susanti; Lucia Maria Santoso (Jurnal Pembelajaran Biologi: Kajian Biologi dan Pembelajarannya, 2016)
Abstract: The aims of the research is to know the influence of Problem Based Learning Model by Edmodo assisted in blood circulation system to XI students’ achievement at SMA Negeri 8 Palembang. The research method was Pre-Eksperimental method  and use One Group Pretest-Posttest Design. The sample in this research was taken by Simple Random Sampling technique. Data conducted at XI MIPA 2 class with amount of 37 students. Instrument were used in this research is test instrument used multiple choice and essay. Test instrument’s data was analyzed by statistical analysis t-test. Based on result of statistical analysis t-test at the level of significant = 0,05, it is shown that tvalues greater than ttable were 32,34 > 1,69, with the result that zero hypothesis (H0) was refused and alternative hypothesis (Ha) was accepted, that can be conclude, Problem Based Learning Model by Edmodo assisted can significantly influence to XI students’ learning achievement at SMA Negeri 8 Palembang in subject matter blood circulation. Keywords: Problem Based Learning model, Edmodo, learning achievement